2005
DOI: 10.1158/1078-0432.ccr-05-0247
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Recurrent Germ Line Mutation of the E-Cadherin Gene: Implications for Genetic Testing and Clinical Management

Abstract: Purpose: To identify germ line CDH1 mutations in hereditary diffuse gastric cancer (HDGC) families and develop guidelines for management of at risk individuals. Experimental Design: We ascertained 31 HDGC previously unreported families, including 10 isolated early-onset diffuse gastric cancer (DGC) cases. Screening for CDH1 germ line mutations was done by denaturing high-performance liquid chromatography and automated DNA sequencing. Results: We identified eight inactivating and one missense CDH1 germ line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
124
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 151 publications
(128 citation statements)
references
References 30 publications
2
124
1
1
Order By: Relevance
“…Genetic alterations, as LOH, which seem to be acquired later in HDGC progression, could be then targeted with drugs such as EGFR and ␣5-␤1-integrinblocking antibodies or transforming growth factor-␤-R small synthetic molecules to prevent cells from migrating and metastasis from establishing. [35][36][37][38][39][40] In conclusion, our data support the previously published rate of CDH1 promoter hypermethylation as a 2nd-hit in HDGC primary tumors, and adds LOH as a key mechanism, mainly in metastatic lesions. Because of the concomitance and heterogeneity of these alterations in neoplastic lesions and the plasticity of hypermethylated promoters during tumor initiation and progression, drugs targeting only epigenetic alterations might not be effective, particularly in patients with metastatic HDGC.…”
Section: Discussionsupporting
confidence: 91%
“…Genetic alterations, as LOH, which seem to be acquired later in HDGC progression, could be then targeted with drugs such as EGFR and ␣5-␤1-integrinblocking antibodies or transforming growth factor-␤-R small synthetic molecules to prevent cells from migrating and metastasis from establishing. [35][36][37][38][39][40] In conclusion, our data support the previously published rate of CDH1 promoter hypermethylation as a 2nd-hit in HDGC primary tumors, and adds LOH as a key mechanism, mainly in metastatic lesions. Because of the concomitance and heterogeneity of these alterations in neoplastic lesions and the plasticity of hypermethylated promoters during tumor initiation and progression, drugs targeting only epigenetic alterations might not be effective, particularly in patients with metastatic HDGC.…”
Section: Discussionsupporting
confidence: 91%
“…Heterozygous germline CDH1 mutations have been described in 18-40% of HDGC families [31][32][33][34][35]. The frequency of CDH1 mutations seems to be highly variable, which may be related to the variable incidence of GC across different geographic regions.…”
Section: Genetics Of Hdgcmentioning
confidence: 99%
“…14 Using functional in vitro assays, we demonstrated that cells expressing pathogenic CDH1 missense mutations fail to aggregate and become more invasive, in comparison with cells expressing wild-type (WT) E-cadherin, 5,12,[15][16][17][18][19][20][21][22] supporting their pathogenic relevance.…”
Section: Introductionmentioning
confidence: 83%
“…5,12,[15][16][17][18][19]21 The slow aggregation assay showed that all the mutants have an impact on the cell-cell adhesion ability but the type of aggregation showed distinct phenotypes (Figure 7a). Comparing with the compact aggregates formed by the WT E-cadherin-expressing cells, some mutants display smaller cellular aggregates, such as mutants T340A, A634V, R749W, P799R and V832M, and others exhibited a close-to-isolated phenotype, as observed for mutants E757K and E781D, very similar to the phenotype of Mock cells.…”
Section: Cdh1 Missense Mutations Affect E-cadherin Subcellular Localimentioning
confidence: 99%